1999
DOI: 10.1021/ic981338l
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Electronic Structure in Polypyridyl Complexes Containing Unsymmetrical Ligands

Abstract: Step-scan Fourier transform infrared absorption difference time-resolved (S(2)FTIR DeltaA TRS) and time-resolved resonance Raman (TR(3)) spectroscopies have been applied to a series of questions related to excited-state structure in the metal-to-ligand charge transfer (MLCT) excited states of [Ru(bpy)(2)(4,4'-(CO(2)Et)(2)bpy)](2+), [Ru(bpy)(2)(4-CO(2)Et-4'-CH(3)bpy)](2+), [Ru(bpy)(4,4'-(CO(2)Et)(2)bpy)(2)](2+), [Ru(4,4'-(CO(2)Et)(2)bpy)(3)](2+), [Ru(bpy)(2)(4,4'-(CONEt(2))(2)bpy)](2+), [Ru(bpy)(2)(4-CONEt(2)-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
36
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 47 publications
(59 reference statements)
13
36
0
Order By: Relevance
“…[Ru (III) (bpy) À (bpy) 2 ] 2+ ) and thus charge is localized on one of three ligands and the charge localization occurs on a femtosecond timescale. [12][13][14][15][16][17][18][19][20][21] Symmetry breaking via vibrational trapping or solvent fluctuation has been proposed as the possible mechanism for charge localization. 22 Though ultrafast dynamics of the prototype [Ru(bpy) 3 ] 2+ have been extensively studied to discern ISC, vibrational relaxation and charge localization processes, real time dynamics studies of mixed ligand (heteroleptic) complexes have not been extensively undertaken and studies on such complexes has gained impetus in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…[Ru (III) (bpy) À (bpy) 2 ] 2+ ) and thus charge is localized on one of three ligands and the charge localization occurs on a femtosecond timescale. [12][13][14][15][16][17][18][19][20][21] Symmetry breaking via vibrational trapping or solvent fluctuation has been proposed as the possible mechanism for charge localization. 22 Though ultrafast dynamics of the prototype [Ru(bpy) 3 ] 2+ have been extensively studied to discern ISC, vibrational relaxation and charge localization processes, real time dynamics studies of mixed ligand (heteroleptic) complexes have not been extensively undertaken and studies on such complexes has gained impetus in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…6) is expected based on previously reported studies of Ru II complexes with similar secondary amide substituents. Meyer and co-workers, [62] as well as George et al [5] have reported an analogous shift in the emission due to the slight electron-withdrawing character of the amide linkage (in these examples, the amide carbonyl was linked to the pyridine ring). In the case of the sec-amL ligand, attachment of the amide linkage to the pyridine ring via the amide N atom should result in a slight increase in the energy level of the acceptor (bipyridine) HOMO; producing a narrowing of the HOMO-LUMO gap, and a corresponding bathochromic shift in the emission (and in the ground state absorption spectrum).…”
Section: Photophysical and Excited State Properties Of Homoleptic Commentioning
confidence: 80%
“…In contrast, bidentate ligands can have different groups bonded to the donor atoms, making them unsymmetrical. Many examples of unsymmetrical ligands exist, notably: salen ligands (N donor atoms) [11], bypyridine and other bidentate pyridine ligands [12,13], phosphine-carboxylate ligands [3], phosphine-carboxylate ligands [1], phosphine-phosphine oxide ligands [14], phosphine-phosphite ligands [15], phosphinephosphinite ligands [15], and NHC ligands [16]. However, it is uncommon to encounter unsymmetrical phosphine-phosphine ligands [17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%